Optimizing the Growth of Tasikmalaya Honje (Etlingera elatior) Accession Seeds by Implementing Fermentation of Rabbit Urine and Coconut Water - Arrin Rosmala; Selvy Isnaeni; Roza Yunita (JERAMI : Indonesian Journal of Crop Science, 2023)
Organic matter has an important role besides providing macro and micro nutrients to plants, it can also improve environmental quality. The fermentation of rabbit urine and coconut water is expected to optimise the growth of honje seedlings. The aim of this study was to determine the concentration of fermented rabbit urine and coconut water that can optimise the growth of honje seedlings of Tasikmalaya accession. The study used a completely randomised design with seven treatments, namely A = control, B = 25% rabbit urine fermentation, C = 50% rabbit urine fermentation, D = 25% coconut water, E = 25% rabbit urine fermentation + 25% coconut water, F = 50% rabbit urine fermentation + 25% coconut water, G = 50% rabbit urine fermentation + 50% coconut water. The results showed that the treatments gave significantly different results on shoot emergence, seedling height, seedling diameter, and root crown ratio. Treatment G produced the fastest shoot emergence (6 days), and plant height (10.4 cm). Meanwhile, the widest seedling diameter was produced by treatment B (4.4cm), C (3.9 cm), and treatment G (3.9cm). Treatment C produced the highest root crown ratio of 0.5.